Inclusion and permanence of people with disabilities at school: an overview of schools in the Urban Zone of the Municipality of Itaperuna-RJ (Research, Society and Development, 2020)
There is an urgent need for discussion about the applicability of legal provisions, embodied in the conditions offered for inclusion and school permanence of students with disabilities, contextualized to local issues in an interdisciplinary and plural way, aiming at valuing people with disabilities. In this sense, the present work aims to present and discuss the panorama of the school reality, with regard to Inclusive Education for people with disabilities, in the 22 municipal schools, in the urban area of the Municipality of Itaperuna-RJ. To this end, a questionnaire about the main legal requirements for school inclusion and permanence was used, considering the laws, regulatory and normative criteria, answered by the management of each school unit and the data were evaluated quantitatively and qualitatively. The results indicate that inclusive school practices, in schools in the urban area of the Municipality of Itaperuna, are consistent with the normative principles and instruments of protection and care for people with disabilities. However, despite the fact that it is still a demand that requires revision of specific policies and singular measures / needs, through differentiated service, the Municipality was attentive and committed to the inclusion of people with disabilities in its school space.